Strategies for Promoting Healthcare Workers’ Compliance with Guidelines for Prevention and Control of Hospital-associated Infections - Picheansathian, Wilawan (Thai Journal of Nursing and Midwifery Practice, 2024)
Healthcare-associated infections (HAI) are considered one of the most important healthcare problems because they significantly affect the quality of healthcare and prognosis of patients. However, a large proportion of HAIs are preventable by improving the compliance of healthcare workers (HCWs) with infection prevention and control (IPC) guidelines. Low adherence of HCWs to IPC guidelines is a major obstacle to global efforts to reduce HAIs. Several factors may affect HCWs’ compliance and noncompliance with the IPC measures. Behavior change of HCWs may require various approaches to improve adherence to IPC guidelines. Multifaceted intervention strategies have been found to be more effective in addressing low compliance rates as compared to strategies focused on simple interventions. It requires appropriate strategies and outcome evaluation for continuous improvement.